Designs and Characterization of Subunit Ebola GP Vaccine Candidates: Implications for Immunogenicity - Agnolon, Valentina; Kiseljak, Divor; Wurm, Maria J.; Wurm, Florian M.; Foissard, Charlotte; Gallais, Fabrice; Wehrle, Sarah; Muñoz-Fontela, César; Bellanger, Laurent; Correia, Bruno Emanuel; Corradin, Giampietro; Spertini, François (Frontiers in Immunology, 2020)
The humoral responses of Ebola virus (EBOV) survivors mainly target the surface glycoprotein GP, and anti-GP neutralizing antibodies have been associated with protection against EBOV infection. In order to elicit protective neutralizing antibodies through vaccination a native-like conformation of the antigen is required. We therefore engineered and expressed in CHO cells several GP variants from EBOV (species Zaire ebolavirus, Mayinga variant), including a soluble GP ΔTM, a mucin-like domain-deleted GP ΔTM-ΔMUC, as well as two GP ΔTM-ΔMUC variants with C-terminal trimerization motifs in order to favour their native trimeric conformation. Inclusion of the trimerization motives resulted in proteins mimicking GP metastable trimer and showing increased stability. The mucin-like domain appeared not to be critical for the retention of the native conformation of the GP protein, and its removal unmasked several neutralizing epitopes, especially in the trimers. The soluble GP variants inhibited mAbs neutralizing activity in a pseudotype transduction assay, further confirming the proteins’ structural integrity. Interestingly, the trimeric GPs, a native-like GP complex, showed stronger affinity for antibodies raised by natural infection in Ebola virus disease survivors rather than for antibodies raised in volunteers that received the ChAd3-EBOZ vaccine. These results support our hypothesis that neutralizing antibodies are preferentially induced when using a native-like conformation of the GP antigen. The soluble trimeric recombinant GP proteins we developed represent a novel and promising strategy to develop prophylactic vaccines against EBOV and other filoviruses.